Activated protein C protects from GvHD via PAR2/PAR3 signalling in regulatory T-cells - Ranjan, Satish; Luft, Thomas (Nature Communications, 2017)
Graft-vs.-host disease is a complication of allogenic hematopoietic stem cell transplantation, and is associated with endothelial dysfunction. Here the authors show that activated protein C signals via PAR2/PAR3 to expand Treg cells, mitigating the disease in mice.